SAT0526 ICG-Enhanced Fluorescence Optical Imaging (FOI) Detects Typical Inflammatory Changes in Subjects with Arthralgia and Psoriasis. (23rd January 2014) - Werner, S. G.; Spiecker, F.; Mettler, S.; Lind-Albrecht, G.; Wiemann, O.; Burmester, G. R.; Backhaus, M.; Langer, H.-E.
Abstract : Background: Early diagnosis of psoriatic arthritis (PsA) is a major challenge. ICG-enhanced fluorescence optical imaging (FOI) is a novel technology that enables detection of inflammation in the hands with high sensitivity and specificity comparable to MRI arthrosonography (1 ). Objectives: To report for the first time of FOI in subjects with arthralgia and psoriasis or family history of psoriasis but without signs of clinically established arthritis. Methods: 19 subjects (12 female, 7 male; mean age 43 years, range 15-88) were referred to the early arthritis clinic with cutaneous manifestations of psoriasis or family history of psoriasis and pain in various joints (monarticular, oligoarticular, polyarticular). None had a history of actual or previous arthritis or tendinitis or any signs of active synovitis at clinical examination. FOI was performed following the usual procedure (1 ). The findings were compared to FOI in 8 patients (7 female, 1 male, mean 53 years, range 29-70 years) with very early PsA (mean disease duration of 8 weeks, range 1-12 weeks). Results: FOI displayed inflammatory changes in all subjects. Joint-related signal intensities were seen in 19/19 (100%), and extraarticular increases signal intensities in 17/19 sequences (89%). The morphology of FOI inflammation (figure 1 right) was indistinguishable from the findings that were seen in patients with very early PsA (figure 1 left) and showed a marked difference compared to FOI in healthy subjects. 5/19 individuals (26%) without clinical symptoms in the hands had positive FOI changes in all small joint regions (wrist, MCP, PIP, DIP). 17/19 FOI findings (89%) showed a triangular, slightly accurate enhancement in projection of the synovio-entheseal complex (2 ) that may be pathognomonic for PsA (1 ). Image/graph: Conclusions: The detection of typical inflammatory changes in subjects with cutaneous manifestations of psoriasis or family history of psoriasis and joint pain but without clinical signs of synovitis or tendinitis suggests that a non-arthritic, subclinical disease stage may precede the onset of clinically active PsA. With the visualization of inflammation in those subjects FOI possibly is a new diagnostic opportunity in incipient PsA. Further investigations with follow up examinations to proof this concept are necessary. References: Werner SG, Langer HE*, Ohrndorf S*, Bahner M, Schott P, Schwenke C, Schirner M, Bastian H, Lind-Albrecht G, Kurtz B, Burmester GR, Backhaus M.*equal contribution: Inflammation assessment in patients with arthritis using a novel in vivo fluorescence optical imaging technology. Ann Rheum Dis. 2012 Apr;71(4):504-10 McGonagle D, Lories RJ, Tan AL, et al. The concept of a "synovio-entheseal complex" and its implications for understanding joint inflammation and damage in psoriatic arthritis and beyond. Arthritis Rheum 2007;56:2482–91. Disclosure of Interest: None Declared